Logotherapy to Increase Self Esteem of Patient With Paraparese Inferiors - Setyaningrum, Dewi; Rachmah Nur Anganthi, Nisa (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: This study aims to determine the clinical feature of Paraparese Inferior Thoracal Stenosis V TH 1-2 patients who have low self-esteem and obtain results from logotherapy. Paraparese Inferior Thoracal Stenosisis a loss of motor function of both legs which causes the patient to not be able to support the body. The problem which is often experienced by persons with body disabilities such as paraparese patients is low self-esteem. Methodology: The research method in this study is a single case design. Data collection using interview methods (auto anamnesis and allow anamnesis), observation, and psychological tests including personality tests (DAP, BAUM, HTP, Warteg Test and Sack’s Sentence Completion Test). The intervention applied was logotherapy. Results: The results of the intervention show that the increase in self-esteem is strengthened by the results of the pre-test in low conditions, while the post-test score is included in the category of high self-esteem by using the Rosenberg Self Esteem Scale (RSES). The prognosis for the subject is bonam, where self-esteem is increasing. Conclusions from the results of the intervention show that logotherapy can improve self-esteem of patients with paraperese. Finally, the study pointed out that logotherapy interventioncan improve self-esteem of patients with paraperese. this is because despite the physical limitations possessed by the patient, the patient is able to find the meaning of his life so that he can carry out activities again Applications/Originality/Value: Logotherapy needs to be trained for care giver health professionals